Palladium-Catalyzed Interceptive Decarboxylative Addition of Allyl Carbonates with Carbonyl Group - Baiju, T. V.; Joseph, Nayana; Ajit, Jainu; Prakash, Praveen; Radhakrishnan, K. V.; Varughese, Sunil; Yamamoto, Yoshinori (Synlett, 2014)
The first palladium-catalyzed interceptive decarboxylative 1,4-addition of allyl carbonates with squarates is reported. Interestingly, the C-3 carbonyl group of N-substituted isatins undergoes smooth decarboxylative 1,2-addition with allyl carbonates. This transformation offers a straightforward method for the synthesis of spiro-oxepane-fused 2-oxindole.
Keywords: palladium; allylation; conjugate addition; allyl complexes; spiro compounds; metathesis